Heterogeneously tempered martensitic high strength steel by selective laser melting and its micro-lattice: Processing, microstructure, superior performance and mechanisms. (15th September 2019) - Li, Xinwei; Tan, Yong Hao; Willy, Habimana Jean; Wang, Pan; Lu, Wanheng; Cagirici, Mehmet; Ong, Chun Yee Aaron; Herng, Tun Seng; Wei, Jun; Ding, Jun
Abstract: Herein, we report the selective laser melting of AISI 4130 high strength steel and its micro-lattice with superior energy absorption capabilities based on a dual material processing and structural design approach. Bulk 4130 was printed to high part qualities with an excellent combination of tensile properties of 1243 ± 25 MPa yield strength, 1449 ± 19 MPa ultimate tensile strength and 15.5 ± 1.5% fracture elongation. Such performance derives from its unique microstructure consisting of an alternating enhanced tempered and well-retained martensitic network. Experiments and simulation reveal the unique microstructure to result from a single-step fusion and quenching process followed by an in-situ rapid dynamic tempering that is associated with the laser scanning patterns. Based on these mechanical properties, orthogonally isotropic micro-lattices were designed and structurally optimized through finite element modelling. Superior per unit weight and volume energy absorption are measured; ranging from 13 to 35 J/g and 12–76 J/cm 3 for relative densities of 10–30% respectively along with high energy absorption efficiencies of ~80%. These excellent properties in turn derive from the synergistic design and material properties. This work demonstrates the potential combination of additive manufacturing and design to create microstructure-geometric specific lattice materials for high performance energy absorption applications. Graphical abstract: Unlabelled Image Highlights: AISI 4130 steel with excellent tensile properties fabricated using selective laser melting Properties derive from an unique microstructural network of alternating enhanced tempered and well-retained martensite A single-step quench and immediate subsequent in-situ dynamic tempering process result in this microstructural arrangement Designed 4130 micro-lattices demonstrate superior energy absorption characteristics given the high strength and ductility Demonstrates the potential combination of additive manufacturing and design towards high performing micro-lattices